Strategic Management of innovative development of energy companies - Y. Alexandrov (Вестник университета)
Backlog of Russian energy companies in terms of equipment with modern equipment and technologies determines the relevance of the transition to an innovative path of development of the sector and the creation of effective innovative development control system. The article describes the stages of construction of innovative development management system, taking into account the strategic implications of management decisions.